Moslem Millennials Donor Intention Through Donation-Based Crowdfunding in Indonesia - Moh. Helmy Najih Ramadhan; Achsania Hendratmi (Universitas Airlangga, 2023)
ABSTRACT: The existence of donation-based crowdfunding as an alternative fundraising system in Indonesia has a great opportunity to keep growing. The millennials as a digitally-native generation should actively contribute to the development of donation-based crowdfunding. This study tries to identify the effect of the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, sense of trust, and experience expectation on the intention to donate donation-based crowdfunding by the Muslim millennials in Indonesia. Respondents who were analyzed were 156 people who were selected using purposive sampling and tested using SmartPLS. The results showed that Social Influence, Sense of Trust, and Experience Expectation had a positive influence on Intention to donate to donation-based crowdfunding. However, a test of Performance Expectancy, Effort Expectancy, and Facilitating Conditions shows that there are different findings. The data presented in this study is expected to add new perspectives for relevant stakeholders to develop donation-based crowdfunding in Indonesia. Keywords: Donation-based Crowdfunding, Moslem Millennials, Partial Least Square, Donation. ABSTRAK: Kehadiran donation-based crowdfunding sebagai alternatif sistem penggalangan dana di Indonesia memiliki peluang yang besar untuk terus berkembang. Generasi milenial sebagai generasi yang terbiasa dengan teknologi seyogyanya berperan aktif dalam perkembangan platform donation-based crowdfunding. Penelitian ini bertujuan untuk mengidentifikasi pengaruh variabel performance expectancy, effort expectancy, social influence, facilitating conditions, sense of trust serta experience expectation terhadap intention to donate to donation-based crowdfunding dari para generasi milenial muslim di Indonesia. Responden yang dianalisis sejumlah 156 orang yang dipilih menggunakan teknik purposive sampling serta diuji menggunakan SmartPLS. Hasil penelitian menunjukkan Social Influence, Sense of Trust, dan Experience Expectation memiliki pengaruh positif terhadap Intention to donate to donation-based crowdfunding. Namun, pengujian pada Performance Expectancy, Effort Expectancy, dan Facilitating Conditions menunjukkan hasil yang berbeda. Data yang ditampilkan dalam penelitian ini diharapkan menambah sudut pandang baru bagi stakeholder terkait agar dapat mengembangkan donation-based crowdfunding di Indonesia. Kata Kunci: Donation-based Crowdfunding, Generasi Milenial Muslim, Partial Least Square, Donasi. DAFTAR PUSTAKA Achmad, R. W., Poluakan, M. V., Dikayuana, D., Wibowo, H., & Raharjo, S. T. (2019). Potret generasi milenial pada era revolusi industri 4.0. Focus: Jurnal Pekerjaan Sosial, 2(2), 187-197. doi:10.24198/focus.v2i2.26241 Ajzen, I. (1991). The theory of planned behavior. Organizational Behavior and Human Decision Processes, 50, 179-211. doi:10.1016/0749-5978(91)90020-t Ardiansyah, D. O. (2016). Pengaruh komunikasi terhadap kinerja karyawan dengan dimediasi oleh kepuasan kerja (Studi pada bagian produksi pabrik kertas pt. setia kawan makmur sejahtera tulungagung). Jurnal Bisnis dan Manajemen, 3(1), 16-30. doi:10.26905/jbm.v3i1.70 Asosiasi Penyelenggara Jasa Internet Indonesia. 2020. Laporan Survei Internet APJII 2019 – 2020 (Q2). Jakarta: Asosiasi Penyelenggara Jasa Internet Indonesia. Az-Zuhaili, Wahbah. (2011). Fiqih Islam Wa Adillatuhu (Vol. 3). Jakarta: Gema Insani. Baptista, G., & Oliveira, T. (2015). Understanding mobile banking: The unified theory of acceptance and use of technology combined with cultural moderators. Computers in Human Behavior, 50, 418-430. doi:10.1016/j.chb.2015.04.024 Bekkers, R. (2003). Trust, accreditation, and philanthropy in the Netherlands. Nonprofit and Voluntary Sector Quarterly, 32(4), 596–615. doi:10.1177/0899764003258102 Belleflamme, P., Lambert, T., & Schwienbacher, A. (2013). Crowdfunding: Tapping the right crowd. Journal of Business Venturing, 29(5), 585–609. doi:10.1016/j.jbusvent.2013.07.003 Bhawika, G. W. (2017). Risiko dehumanisasi pada crowdfunding sebagai akses pendanaan berbasis teknologi di Indonesia. Jurnal Sosial Humaniora, 10(1), 47-58. doi:10.12962/j24433527.v10i1.2355 Choy, K., & Schlagwein, D. (2015). IT affordances and donor motivations in charitable crowdfunding: The